Bibliometric analyses of factors influencing color preferences in urban environmental spaces - Qu, Chunshuo; Dong, Jianfei; Wang, Weijia (Frontiers in Psychology, 2025)
Urban color is a crucial visual component of urban aesthetics, directly reflecting national traditional aesthetic consciousness and historical culture, and holding significant aesthetic value and research relevance. As a key factor in urban color studies, color preference significantly impacts human behavior and plays a vital role in urban planning and development. However, a comprehensive and systematic understanding of urban color preferences remains underexplored. This study examines 379 relevant studies using bibliometric review methods and literature visualization tools, classifying, and synthesizing them according to research hotspots and fields. Four primary categories influencing urban color preference were identified: personal attributes, socio-cultural influences, environmental space, and dynamic factors. The analysis also highlights the psychological mechanisms underlying color preference, including its effects on emotional regulation, cognitive processing, and social identity. The findings contribute to the field by offering a data-driven framework for understanding urban color preferences and proposing practical applications for urban planning. The study emphasizes the importance of color preference in promoting human well-being and sustainable urban development, with implications for future interdisciplinary research.